Both parents migrating and left-behind children’s cognitive ability in rural China: does it pay? - Yao, Mengzhu (Frontiers in Public Health, 2024)
While the well-documented negative correlation between both parents migrating and the academic performance of left-behind children (LBC) in rural China is widely acknowledged, it's important to recognize that statistical data reveals millions of children experiencing both parents migrating. This discrepancy between the documented negative impact and the prevalence of both parents migrating can be attributed to previous studies primarily focusing on the direct effects. By employing national representative panel data to address the endogeneity issue, this study demonstrates that the initially observed negative direct impact of both parents' migrating can be completely offset by the indirect impact channels, including private tutoring, family tutoring, family income, and boarding school participation. In contrast to prior research, this study unveils a positive overall impact of both parents' migration on LBC's school performance.